Smooth and rough platinum deposits resulting from the electroreduction of hydrous oxide platinum overlayers : A mechanistic approach - Bolzán, Agustín Eduardo (1988)
The electroreduction of thick platinum oxides accumulated by the application of a fast square wave perturbing potential in 0.5 M H2SO4 was studied by using potentiodynamic and potentiostatic techniques complemented with scanning electron miscroscopy. The electroreduction process can be unambigously explained through an instantaneous nucleation and 3-D growth of right circular cones under charge transfer control where diffusion of reacting species to the growing centres is essential for further expansion. The growth mode of the Pt crystallites either smooth or rough depends on the electroreduction conditions. The rought/smooth modes of growth result from the influence of the electric field on the transport of particles in the reaction region and on the supersaturation concentration operating during the electrocrystallization process.